(untitled) (Proceedings of the World Disability & Rehabilitation Conference, 2019)
Provision of care to a child with Cerebral Palsy (CP) requires individualized assessment and management of all associated problems. They need special education and their families need social support to face day-to-day demands of caregiving. We reviewed the characteristics of 375 children with CP attending Teaching Hospital, Karapitiya to identify their health problems and current level of health and social care utilization. Data were collected through questionnaire-based interviews with caregivers or extracted from child’s medical records. The results revealed that approximately 2/3rd of the children had spastic quadriplegic CP and 54% had some co-morbidity. The majority (30.9%) had 3-4 functional problems. Problems with mobility (77.6%), social activities of daily living (69.3%), bladder/bowel function (70.4%) and speech (57.9%) were the common functional problems. Learning difficulties were reported in 29.3%. Nearly 17% had behavioural and emotional problems. Approximately 98% of the children received physiotherapy. Despite higher numbers having problems with speech and activities of daily living, only 48% received speech therapy and less than 10% received occupational therapy. Among pre-school and school age children, over 70% had never attended school. Only 17.2% of school attendees received special education. Although nearly 70% was from rural, low socio-economic backgrounds, only 12.8% received any form of external financial support. We conclude that children with CP and their families have many unmet needs in the areas of therapy, special education and social support. These needs should be addressed adequately in developing long-term care plans for children with CP, in order to achieve better outcomes.